2011
DOI: 10.1182/blood-2010-01-265272
|View full text |Cite
|
Sign up to set email alerts
|

STAT6 signaling pathway activated by the cytokines IL-4 and IL-13 induces expression of the Epstein-Barr virus–encoded protein LMP-1 in absence of EBNA-2: implications for the type II EBV latent gene expression in Hodgkin lymphoma

Abstract: IntroductionEpstein-Barr virus (EBV) is a ␥-herpes virus of the Lymphocryptovirus genus that has succeeded to colonize Ͼ 90% of the adult population. 1 As a general characteristic of these viruses, they can all infect and immortalize B-lymphocytes in vitro. The in vitro EBV-infected B cells proliferate and give rise to lymphoblastoid cell lines (LCLs). The pattern of latent EBV gene expression seen in LCLs is referred to as the type III latency, in which 9 virally encoded proteins are expressed (EBV nuclear an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
47
2

Year Published

2012
2012
2018
2018

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 62 publications
(51 citation statements)
references
References 47 publications
(59 reference statements)
0
47
2
Order By: Relevance
“…LMP1 is induced by CD4 ϩ T cell-derived cytokines like IL-4, IL-10, IL-13, and IL-21 (18)(19)(20), which is probably the mechanism through which the T cells provide help for the in vitro growth of the infected B cells. IL-6 is another cytokine known to be a growth factor for EBV-infected B cells (43).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…LMP1 is induced by CD4 ϩ T cell-derived cytokines like IL-4, IL-10, IL-13, and IL-21 (18)(19)(20), which is probably the mechanism through which the T cells provide help for the in vitro growth of the infected B cells. IL-6 is another cytokine known to be a growth factor for EBV-infected B cells (43).…”
Section: Discussionmentioning
confidence: 99%
“…For survival and proliferation of the EBV-carrying type IIa cells, inter-actions with the microenvironment are required (17). Results from our laboratory have shown that a number of cytokines (interleukin-4 [IL-4], IL-13, and IL-21) contribute to the induction of expression of LMP1 (18)(19)(20) and probably help the survival and proliferation of latency IIa cells in vivo.…”
mentioning
confidence: 99%
“…Cytokines, such as interleukin-4 (IL-4), IL-6, IL-10, IL-13, and IL-21, have been frequently reported to activate the JAK/ STAT pathway, thereby inducing LMP1 gene expression through STAT (23)(24)(25)(26)(27)(28). In certain latency II infected cells, including NPC cells (29), LMP1 transcription originates from a STAT regulated upstream promoter, termed TR-L1p, located within the terminal repeats (TRs), in addition to the proximal ED-L1p (23,24,27,30,31). We previously identified a CCAAT enhancer-binding protein (C/EBP) family transcription factor that augments both proximal and distal promoter activation of LMP1 in type II latency by binding to a sequence motif in the proximal promoter (32).…”
mentioning
confidence: 99%
“…LMP-1 plays a central role in EBV biology, since it acts in part as a constitutively active CD40 receptor analog and is essential for B cell proliferation and transformation by EBV (24). In type III latency, EBNA-2 is the major transactivator of the LMP promoters, while in type II latency, depending on the cellular context, different cytokines , are responsible for the activation of LMP-1 transcription (20,26,27,28).Type I interferons (IFNs) are produced in relatively large amounts in response to pathogen sensing by the innate immune system (46). In addition to their direct antiviral activities, these proteins also have antiproliferative and immunomodulatory properties.…”
mentioning
confidence: 99%